Elevated triglyceride-glucose index predisposes to the initial episode of peritonitis in chronic peritoneal dialysis patients - Guiling Liu; Qiqi Yan; Ruifeng Wang; Dandan Li; Jingjing Cong; Xiaoli Chen (Renal Failure, 2023)
Objective The serum triglyceride-glucose (TyG) index is a marker of inflammation. However, the relationship between TyG index and peritoneal dialysis-related peritonitis (PDRP) is unclear. This study aimed to investigate the potential relationship between the baseline TyG index and the initial episode of PDRP.Methods A total of 208 peritoneal dialysis (PD) patients were enrolled from January 1, 2012, to December 31, 2019 and followed up until December 31, 2022. They were divided into 2 groups according to the median TyG. The primary outcome was the occurrence of the initial episode of PDRP while on PD therapy. Kaplan-Meier curves and Cox regression analyses were used to examine the association between them.Results Eighty-five initial episodes of PDRP were identified. The risk of PDRP was higher in the high-TyG index group (p = 0.030). Multivariate Cox regression analysis showed a higher risk of PDRP in patients with a high TyG index (HR = 1.800, 95% CI 1.511–2.815, p = 0.010).Conclusion The baseline serum TyG index was an independent risk factor for the initial episode of PDRP in chronic PD patients.